Knowledge and Teaching Competencies of Physical Education Teachers on Students with Special Needs in the Central Region, Ghana (Baltic Journal of Sport and Health Sciences, 2024)
Background: This research investigated the inclusion of students with special needs during Physical Education lessons in the Central Region, Ghana. Many learners only observe during Physical Education lessons because the teachers simply ignore them or are challenged with how to integrate them into the lessons. There were also challenges with the nature of the facilities and equipment available for lesson delivery.Methodology: A concurrent research design was used thus, combining both quantitative and qualitative approaches. The design selected presents the best perspective of the issues. Participants were made up of 230 respondents sampled from Senior High Schools purposively consisting of 116 Physical Education teachers and 114 students with disabilities. The qualitative data was thematically analysed according to the objectives. Chi square was used for the analysis of the quantitative data.Results: Many Physical Education teachers perceived inclusive Physical Education as a right to full participation for every learner; therefore, expected full participation by all students irrespective of their physical, mental status, sex orientation ethnic origin but confirmed that they did not have adequate knowledge, expertise and are challenged in other ways to successful integrate students with special needs at their lessons.Conclusion: Physical Education teachers perceived inclusive education as a right for everyone including persons with disability. Though they had some training in inclusive education, they were not equipped enough to handle persons with special in their PE lessons to the appreciable level. They supported the idea of including students with special needs during their lessons due to the benefits they will gain but of the opinion that this most often disrupts the harmony of their teaching because they are unable to handle them the best way.Keywords Inclusive Education, Physical Education Lessons, Students with special needs, In-Service Training